Innovating the management of mites on strawberry crops - Vacacela Ajila, Henry Eduardo (2018)
Two species of pest mites are responsible for causing great losses in strawberry production. The main one, the two-spotted spider mite Tetranychus urticae Koch (Acari: Tetranychidae), may cause losses up to 80%. On the other hand, the cyclamen mite Phytonemus pallidus (Banks) (Acari: Tarsonemidae) is also an important pest in strawberry. Although it has not previously been reported in Brazil, this pest is commonly associated with strawberry crops in several countries in the world. Therefore, in this study, initially, we report the occurrence of this new pest on strawberry in Minas Gerais- Brazil. Subsequently, we examined the suitability of different pollen sources as supplementary food for the predatory mite N. californicus (McGregor) (Acari: Phytoseiidae) when the population of its prey T. urticae is low. Additionally, we investigated the relative suitability of different pollen types for N. californicus survival and reproduction, and the life history impacts of a mixed diet of pollen and prey. Then, we assessed the population dynamics of T. urticae on strawberry plants in the presence of the N. californicus, with or without pollen, and in comparison to the specialist predatory mite P. macropilis (Banks) (Acari: Phytoseiidae). Further, we evaluated the toxicity of the lime sulfur to the phytophagous mite T. urticae and its natural enemies P. macropilis and N. californicus. In the same study, we evaluated the effect of sublethal concentrations of lime sulfur over oviposition, egg viability and foraging behaviour of those three mite species. Lastly, we studied the effect of ultraviolet (UV) irradiation on female mortality and egg sterility of T. urticae. We investigated whether inactive mites (females and eggs of T. urticae) may have negative effects on the biological parameters of the predatory mites N. californicus and P. macropilis. The main results of this study showed that P. pallidus was found in organic strawberry crops in two municipalities in the state of Minas Gerais. We confirmed that N. californicus is an efficient biological control agent of T. urticae in strawberry crop and the provision of supplementary food could retain them in the crop prior to the arrival of the pest or in periods of prey scarcity. Additionally, we found that lime sulfur exhibited higher toxicity to the predators N. californicus and P. macropilis than to T. urticae. On the other hand, the exposure to field-applied concentrations resulted in higher reductions on the oviposition rate of T. urticae than on the predatory mites. Interestingly, although the egg viability of P. macropilis was less affected by such lime sulfur exposures, these mites were unable to avoid lime sulfur-treated areas. Finally, we proved that UV irradiation has a negative effect on the phytophagous mite T. urticae causing sterility of the eggs and the mortality of the females. Both predatory mites N. californicus and P. macropilis can feed on females and sterile eggs of T. urticae without affecting their biological parameters. So, this process can improve mass rearing and could be used in several biological control systems.